P231 Efficacy of the invasive diagnostic tests in symptomatic helicobacter pylori infected children: a single centre study. (6th June 2017) - Hurduc, Victoria; Bordei, Luiza; Toma, Varvara; Plesca, Doina
Abstract : Introduction: H pylori is usually acquired mostly in childhood and leads to prolonged exposure to this potentially carcinogenic agent. Aim: The aim of this study was to evaluate the accuracy of invasive diagnostic tests for H pylori infection in symptomatic infected children who were referred for endoscopic evaluation and to analyse the prevalence of selected virulence genes ( cag A, vac A, ice A). Pacients and methods: We conducted a prospective study of 300 consecutive symptomatic children (age range 1–18 years) with uninvestigated dyspepsia and extradigestive signs suggestive for an organic disease requiring a first upper gastrointestinal endoscopy. The gastric biopsy specimens were evaluated by rapid urease test, histological examination, culture and polymerase chain reaction (PCR). The sensitivity, specificity, predictive positive value (PPV) of the invasive tests used, were evaluated. Statistical analysis were performed using the Graph Pad Prism Program. Results: Active H pylori infection was documented in 145 of the 300 studied children (48, 33%): Endoscopic nodular gastritis was identified in most of the cases (105/145 patients; 72, 41%). The rapid urease test was positive in 115 children (sensitivity 85, 19%, specificity 93, 94%, PPV 92%) and histopathology in 129 cases, with a higher sensitivity (89, 58%) and VPP (99, 23%). Culture was performed in 108 cases, with the lowest sensitivity results (74, 48%) but with higher specificity (100%) and VPP (100%). There was no difference in specificity and PPV between histology and culture, as opposed to RUT, in which case they were lower. H pylori infection virulence genotype was analysed by conventional PCR which was positive 140/145 infected children with higher levels of specificity (100%) and VPP (100%), which were significantly higher compared to other invasive tests used in this study. The cag A gene was positive in 96 cases, compared with vac A gene which was identified in all 140 cases isolated by PCR with the predominant vacA s1/m1 genotype (86/140 cases; 61, 42%). H pylori strains positive for ice A1 gene were identified in 100/140 cases (71, 42%), which were associated with the most virulent genotypes ( vac A s1/m1 and vac A s1/m2 ). Conclusions: Our data suggest that among invasive test PCR had a significantly higher sensitivity, specificity (p<0, 0001) compared with other invasive tests. There was no difference in specificity and PPV between histology and culture, as opposed to RUT, in which case they were lower.